Asparagus densiflorus ‘Myers’ Myers Asparagus Fern: FPS-52/FP052, 8/2018 - Gilman, Edward; Klein, Ryan W.; Hansen, Gail (EDIS, 2018)
This document provides a detailed overview of the ‘Myers’ asparagus fern (Asparagus densiflorus ‘Myers’), a perennial herb known for its fine texture and upright habit1. It describes the plant’s physical characteristics, including its scale-like true leaves, light green cladophylls, and bright red berries. The document also covers the plant’s growth requirements, such as light, soil, and water needs, and highlights its uses in landscaping and indoor settings. Additionally, it mentions the plant’s moderate drought tolerance, good soil salt tolerance, and lack of serious pest issues.